2014
DOI: 10.1590/2317-1782/201420140476
|View full text |Cite
|
Sign up to set email alerts
|

Association between pharyngeal residue and posterior oral spillage with penetration and aspiration in Stroke

Abstract: PURPOSE: This study aimed at showing association between the posterior oral spillage and pharyngeal residue with tracheal aspiration and/or laryngeal penetration in stroke. METHODS: Clinical cross-sectional retrospective multicenter study. The study included 63 videofluoroscopic tests of post-ischemic stroke individuals and oropharyngeal dysphagia data of the three reference centers providing care for patients with dysphagia (43 men and 20 women; age range: from 40 to 90 years). These individuals were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
1
9
0
3
Order By: Relevance
“…In agreement with these studies, although without identifying the quantity and location of pharyngeal residues or the differences among the various dysphagic groups, the present study observed that the frequency of occurrence of pharyngeal residues of the food consistencies studied in neurogenic oropharyngeal dysphagia was higher than the absence of such event. Considering that the presence of pharyngeal residues is related to distinct types of impairment of various biomechanical actions of oropharyngeal swallowing that depend both on oral propulsion and on mechanisms of pharyngeal contraction and the opening of the pharyngoesophageal transition, the possibility of this being a frequent finding in dysphagic symptomatology is considerable and agrees with the literature (18,19,22) . Thus, even though there is consensus in the literature about the frequent presence of pharyngeal residues among subjects with neurogenic oropharyngeal dysphagia, little is known about the quantity or site of occurrence of this event in different populations.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In agreement with these studies, although without identifying the quantity and location of pharyngeal residues or the differences among the various dysphagic groups, the present study observed that the frequency of occurrence of pharyngeal residues of the food consistencies studied in neurogenic oropharyngeal dysphagia was higher than the absence of such event. Considering that the presence of pharyngeal residues is related to distinct types of impairment of various biomechanical actions of oropharyngeal swallowing that depend both on oral propulsion and on mechanisms of pharyngeal contraction and the opening of the pharyngoesophageal transition, the possibility of this being a frequent finding in dysphagic symptomatology is considerable and agrees with the literature (18,19,22) . Thus, even though there is consensus in the literature about the frequent presence of pharyngeal residues among subjects with neurogenic oropharyngeal dysphagia, little is known about the quantity or site of occurrence of this event in different populations.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have identified and characterized the presence of pharyngeal residues in neurogenic oropharyngeal dysphagia, relating them to the presence of laryngotracheal aspiration (18,19,21,24,25) . In agreement with these studies, although without identifying the quantity and location of pharyngeal residues or the differences among the various dysphagic groups, the present study observed that the frequency of occurrence of pharyngeal residues of the food consistencies studied in neurogenic oropharyngeal dysphagia was higher than the absence of such event.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, even though the pureed and thickened liquid food consistencies can be considered to be the safest ones for patients with some other neurological diseases, it is of fundamental importance to remember that the present sample of ALS patients was the one that most frequently produced pharyngeal residues, a fact that may potentiate the risk of aspiration (27) .…”
Section: Discussionmentioning
confidence: 95%